Magnesium deficiency score predicts erectile dysfunction risk and mortality: a population-based analysis of NHANES 2001–2004 - Chen, Xiaobao; Weng, Kangqiang; Xie, Ruoyun; Lin, Junwei; Liu, Lingjun; Zhu, Shaoxing; Zheng, Huaiying (Frontiers in Nutrition, 2025)
BackgroundMagnesium deficiency is associated with numerous cardiovascular and metabolic disorders, which are established risk factors for erectile dysfunction (ED). However, the role of the magnesium depletion score (MDS)—a composite measure of magnesium status—in relation to ED and subsequent mortality remains unclear.MethodsWe analyzed data from 3,917 participants in the National Health and Nutrition Examination Survey (NHANES) 2001–2004. Weighted multivariable logistic and Cox proportional hazards models were used to examine associations between MDS and ED and between MDS and mortality, respectively. Sensitivity analyses included subgroup analyses and propensity score matching.ResultsOf the participants, 1,090 were identified with ED. During follow-up, 654 deaths occurred. After full adjustment, each 1-point increase in MDS was associated with a 37% higher prevalence of ED (OR = 1.37, 95% CI: 1.16–1.62). Among those with ED, higher MDS was also associated with a 30% increased risk of all-cause mortality (HR = 1.30, 95% CI: 1.17–1.45). Sensitivity analyses supported the robustness of these findings.ConclusionHigher MDS is significantly associated with both increased prevalence of ED and greater all-cause mortality in men with ED. These results underscore the importance of assessing magnesium status as a potential target for risk stratification and nutritional intervention in the management of ED.